The Effect of Texts-Based Interactional Feedback (TIF) on the Students’ EFL Writing - Warsidi Warsidi (Yayasan Visi Intan Permata, 2017)
This study is reporting the results of the TIF implementation in a student’s students’ EFL writing. It evaluated the student first supervisory paper, the last supervisory paper, and the participant’s perception toward the TIF implementation. This is qualitative study with the linguistic features as the scoring frameworks, including lexical sophistication, syntactic complexity, and rhetorical structure. This boundary study is the participant’s text findings, discussion, and concluding parts. The results of this study revealed that participant’s academic writing changed significantly in the rhetorical structure and tended ignoring the other two scoring frameworks. The study also indicated that the student has intermediate level of English. Then, the participant’s perception toward the TIF implementation also resulted positively.